Salidroside Protects Dopaminergic Neurons by Preserving Complex I Activity via DJ-1/Nrf2-Mediated Antioxidant Pathway - Ruru Li; Songhai Wang; Tao Li; Leitao Wu; Yan Fang; Yang Feng; Lingling Zhang; Jianzong Chen; Xin Wang (Parkinson's Disease)
The pathogenic mechanism of Parkinson’s disease (PD) remains to be elucidated; however, mitochondrial dysfunction at the level of complex I and oxidative stress is suggestively involved in the development of PD. In our previous work, salidroside (Sal), an active component extracted from the medicinal plant Rhodiola rosea L., might protect dopaminergic (DA) neurons through modulating ROS–NO-related pathway. However, the mechanism of Sal-induced neuroprotective effects against PD remains poorly understood. Therefore, we further investigated whether Sal plays neuroprotective effects by activating complex I via DJ-1/Nrf2-mediated antioxidant pathway. The results showed that Sal remarkably attenuated MPP+/MPTP-induced decline in cell viability, accompanied by decreases in reactive oxygen species (ROS), malondialdehyde (MDA), and 8-hydroxy-deoxyguanosine (8-OHdG) contents and increases in the superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px), as well as glutathione (GSH) levels. Furthermore, Sal greatly improved the behavioral performance and prevented the severe reduction of TH-positive neuron numbers in the substantia nigra (SN). Moreover, in comparison with the MPP+/MPTP group, Sal increased the nuclear translocation of DJ-1 and Nrf2 and the mitochondrial translocation of DJ-1, accompanied by activating complex I. Furthermore, silencing of DJ-1/Nrf2 inhibited the increase of complex I activity and cell viability elicited by Sal. Together, these results support the neuroprotective effect of Sal against MPP+/MPTP-induced DA neurons damage.